Determinants of meconium-stained amniotic fluid among laboring mother in Ethiopia, systematic review and meta-analysis - Gashaw, Anteneh; Adamu, Yayeh; Sime, Yohanes; Destaw, Belete (Frontiers in Global Women's Health, 2024)
Background: -M econium-stained amniotic fluid (M SAF) occurs during childbirth when the amniotic fluid carries traces of meconium, the initial stool passed by a newborn. Often signaling fetal distress, M SAF is linked to heightened risks for both the mother and the newborn. In Ethiopia, there is insufficient attention given to this condition. Despite varied study results indicating a considerable range in M SAF occurrences, there is an absence of a comprehensive national overview. Therefore, this systematic review and meta-analysis aim to evaluate the aggregated prevalence of meconium-stained amniotic fluid among laboring mothers and its influencing factors in Ethiopia, providing a consolidated understanding for healthcare strategies and policies.Method:-Following PRISM A guidelines, a systematic review and meta-analysis were executed. Extensive literature searches were conducted on PubM ed, Google Scholar, and African Online Journal databases. The pooled prevalence was estimated using a weighted inverse variance random effect model. Heterogeneity among studies was evaluated through Cochrane Q-test and I2 statistics. To assess publication bias, a funnel plot and Egger's test were performed. The identification of factors associated with meconium-stained amniotic fluid among laboring mothers in Ethiopia was conducted using Stata v 18 software.Result:-In total, 63 articles were initially identified, and ultimately, four articles were deemed suitable for inclusion in this review. The combined prevalence of meconium-stained amniotic fluid among laboring mothers in Ethiopia was determined to be 20% (95% CI: 14-25%). Upon conducting subgroup analysis, it was revealed that the prevalence of meconium-stained amniotic fluid was highest in the Oromia region and lowest in Addis Ababa. Notably, pregnancies complicated by pregnancy-induced hypertension disorder showed a significant association with the presence of meconium-stained amniotic fluid, with an odds ratio of 6.21 (95% CI: 4.04-8.38).In conclusion, this review emphasizes the common occurrence of meconiumstained amniotic fluid (M SAF). Notably, it identifies a significant association between pregnancy complicated by hypertension and the presence of M SAF. This underscores the need for targeted interventions to reduce M SAF incidence and mitigate associated adverse outcomes in the Ethiopian.